Manipulation of food consumption using design language. - Wiryadi, Cindy. (2013)
Most people cannot really figure out how they gain or lose weight when they do not change their eating or exercise patterns. This happens because people are not aware of 90% out of 200 food-related decisions they have to make everyday. They also do not realize that the hidden persuaders, such as food presentation, food packaging, advertising, kitchen design and cutlery actually affect how much they will eat eventually. My project focuses on dinnerware as the hidden persuaders that affect how much people eat at home. By re-designing their details and specification according to Mindless Eating book by Brian Wansink, Ph.D and to how the concept of Illusion works, the improved design will be able to help people to change their eating habits and diet effortlessly.